Chillax Enterprise: edu-playground / Nuha 'Afifah Sharifuddin... [et al.] - Sharifuddin, Nuha 'Afifah; Mohd Fadzli, Nur Aqilah Natasha; Abdull Halim, Nur Ariff Aiman; Md Yazid, Mohammad Fathullah; Mohd Hazizan, Nur Aqilah Syazwana; Shafie, Ainon Khairiah (2017)
Chillax enterprise is to design playground systems that fulfill the physical and mental need of children from 3 to 12 years old while the aims to be number one in sales, number one in brand recall, and number one in promoting the importance and safety of play to all children and adults in the world